Novel methanotrophic community assemblages in a terrestrial methane seep in Svalbard - Fåne, Pernille Maria Skaset (UiT Norges arktiske universitet, 2020)
Recent studies have concluded that groundwater driven methane escape through open system pingos is an important greenhouse gas source in the vulnerable high Arctic. In wetlands and marine sediments, large quantities of methane are consumed by methane oxidizing bacteria (MOB) and ANaerobic MEthanotrophic (ANME) archaea, preventing its release to the atmosphere. The methanotrophic capacity of open system pingos is understudied, and microbial community profiling is of key interest, to infer the magnitude of the methane filter and for high resolution prediction of methane evasion. In this thesis, we mapped the microbial community assemblages across hydrological transitions at the open system pingo Lagoon pingo (N78°14’22 E015°45’16). In summer, methane-saturated and oxygen limited groundwater discharges continuously through a main source, forming crater-like ponds, providing potential habitats for methanotrophy. We sampled sediments in August 2019 and coordinated these with methane flux measurements and oxidation rate assays. Environmental parameters and 16S rRNA gene diversity revealed a radial mosaic of habitat patches, made by the seep water. We found distinct and unusual microbial communities inhabiting these habitat patches, suggesting high levels of specialization and adaptation to an unusual terrestrial system with marine influences. Phylogenetic analyses of 16S amplicons unveiled MOB and ANME communities in the crater pond. The MOB sequences were dominated by the type I genus Methylobacter, which was >97% affiliated to the arctic wetland strain Methylobacter tundripaludum SV97. The highest relative abundances of Methylobacter coincided with methane oxidation rates in waterlogged habitats. The distribution of the MOB could not be explained by any environmental parameters measured in this study alone, however it is likely that the MOB are largely controlled by water and/or the dissolved methane, oxygen and nutrients. Surprisingly, Methylobacter was prevalent in sediments continuously flushed with anoxic ...